Motivating people to sustain healthy lifestyles using persuasive technology: A pilot study of Korean Americans with prediabetes and type 2 diabetes. Issue 4 (April 2019) - Kim, Miyong T.; Kim, Kim Byeng; Nguyen, Tam H.; Ko, Jisook; Zabora, Jim; Jacobs, Elizabeth; Levine, David
Highlights: We tested feasibility of a hybrid diabetes care model in an ethnic minority group. Our model combined a digital touch of mHealth and a human touch of CHWs. About a half (51.5%) lowered their hemoglobin A1C below 6.5% in 6 months. Many (41.2%) stopped/reduced antidiabetic drugs but still managed their diabetes. Weight, depression and blood pressure were also significantly improved. Abstract: Objective: To test the efficacy of a hybrid model of the self-help intervention program (hSHIP), which combines a mobile version of SHIP (mSHIP) and personal coaching, to address unique cultural and motivational factors for optimal self-management of type 2 diabetes and prediabetes among Korean Americans (KAs). Methods: A single-group feasibility study design was used. The hSHIP utilizes texts and motivational counseling based on well-tested intervention content for KAs. To facilitate the dissemination of hSHIP, we developed a web application adopting the principles of persuasive technology to motivate behavior changes. Results: Feasibility assessment found that hSHIP was well accepted by both participants and community health workers who delivered the intervention. An average of 1.3% A1C reduction (from 7.8% to 6.5%) was achieved by KAs with diabetes (n = 165), 51.5% of whom lowered their A1C below 6.5% in 6-months. No one with prediabetes (n = 50) progressed to diabetes. Other clinical outcomes (e.g., weight, depression, and blood pressure) also improved significantly; 41.2% were able to reduce or discontinue antidiabetic drugs. Conclusion: The feasibility and initial efficacy of hSHIP were demonstrated. Practice implication: This hybrid diabetes self-management model is a viable tool for traditionally underserved groups with diabetes or prediabetes.